Communication of genetic information in the palliative care context: Ethical and legal issues. (December 2018) - Saulnier, Katie M.; Cinà, Margherita; Chan, Benny; Pelletier, Sylvie; Dorval, Michel; Joly, Yann
As scientific understanding of the heritable aspects of cancer deepens, the need to effectively communicate genetic information within the families of cancer patients becomes more acute. In the palliative care context, the question of when and how to disclose a patient's genetic information raises a host of ethical, legal, and social issues, including the challenges of communicating during the end-of-life stage and complex familial and cultural dynamics. In this paper, the authors outline the legal components of these issues in three civil law jurisdictions with similarly comprehensive approaches to healthcare and palliative care - Quebec, Belgium, and France - and provide insights from bioethics literature and normative documents on the disclosure of genetic information at the end of life. From this research, the authors propose a strategy for palliative care providers who are considering available options to communicate hereditary health information.